2013
DOI: 10.3111/13696998.2013.772058
|View full text |Cite
|
Sign up to set email alerts
|

Medical costs and healthcare resource use in patients with lupus nephritis and neuropsychiatric lupus in an insured population

Abstract: Subjects with lupus nephritis or NPSLE have high costs and resource use, compared to unaffected controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 19 publications
1
66
2
1
Order By: Relevance
“…Studies from the US have shown that patients with LN incurred annual costs that are 2.5 to 6-fold higher than patients without LN (1,1214). Carls et al reported annual costs were almost 4-fold higher in US patients with LN [$83 869 versus $ 22 188 in those without LN]1 (1) while Furst et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies from the US have shown that patients with LN incurred annual costs that are 2.5 to 6-fold higher than patients without LN (1,1214). Carls et al reported annual costs were almost 4-fold higher in US patients with LN [$83 869 versus $ 22 188 in those without LN]1 (1) while Furst et al .…”
Section: Discussionmentioning
confidence: 99%
“…Carls et al reported annual costs were almost 4-fold higher in US patients with LN [$83 869 versus $ 22 188 in those without LN]1 (1) while Furst et al . reported that patients with LN incurred annual costs of $44 524 versus $7113 in matched controls without SLE (14). A Medicaid study reported lower annual costs, but the differential between those with LN and matched controls without SLE was almost 3-fold [$38 401 versus $12 945] (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations